The benefits of nursing professional governance nursing research and evidenced-based practice councils for new graduate nurses - Cheryl Green; John Brennan; Lauren Koscal; Emma Sears; Jessica Munoz; Evelyn Jacovino; Lauren Thayer; Todd Allen Lane; Elizabeth Dos Santos (Dialogues in Health)
New graduate nurses are an untapped population for nursing professional governance and nursing research and evidenced-based practice councils. New graduate nurses can offer new insights into the management of patient care and nursing workflow. By educating new graduate nurses about the benefits of nursing research and evidence-based practice councils at the start of their careers, an early standard of excellence in the empowerment of applying evidenced-based practice principles to improve patient care quality can occur. This narrative literature inquiry explores new graduate nurses perspective of research and evidence-based practice councils, with the targeted goal of engagement for professional and personal growth as a nurse leader.